Persistence of microcystin production by Planktothrix agardhii (Cyanobacteria) exposed to different salinities. Issue 1 (2nd January 2020) - Vergalli, Julia; Fayolle, Stéphanie; Combes, Audrey; Franquet, Evelyne; Comte, Katia
ABSTRACT: Recent reports predict increases in harmful cyanobacteria in water systems worldwide due to climatic and environmental changes, which would compromise water quality and public health. Among abiotic changes, higher salinities are expected to promote the growth of certain harmful species, such as Planktothrix agardhii, which forms blooms in brackish waters. Since P. agardhii is a common producer of cyanotoxin, we investigated the growth and tolerance of this species when exposed in vitro to a range of salinities, while assessing variations in its microcystin diversity and production in batch cultures during a time-frame experiment spanning 18 days. The study revealed salt acclimation of the brackish P. agardhii, which continued to produce microcystins in salty cultures, while maintaining its growth capacity at low to medium NaCl (ranging from 0 to 7.5 g l −1 ). With higher concentrations (10 to 15 g l −1 ) significantly less growth occurred, corresponding to the shortening of cyanobacterial filaments, which nevertheless maintained their metabolic functions, as revealed by the high intensity of chlorophyll auto-fluorescence and persistent microcystin production. These findings showed that moderate to high salt levels do not inhibit microcystin production by P. agardhii, at least for several weeks. This raises questions concerning the persistence of harmful cyanobacteria in shallow water systems more exposed to evaporation and consequently to an increase in salinity in the future, as predicted by various climate models.